Use of the 27 kDa recombinant protein from Paracoccidioides brasiliensis in the serodiagnosis of paracoccidioidomycosis (1998)
ABSTRACT: Paracoccidioidomycosis (PCM) is one of the most important endemic mycoses in Latin America; it is usually diagnosed by observation and/or isolation of the etiologic agent, Paracoccidioides brasiliensis, as well as by a variety of immunological methods. Although the latter are effective, two circumstances, cross-reactions with other mycotic agents and antigen preparation that is marked by extreme variability among lots, hinder proper standardization of the procedures. To circumvent this lack of reproducibility, molecular biology tools were used to produce a recombinant 27-kDa-molecular-mass antigen from this fungus; a sizable quantity of this antigen was obtained through fermentation of Escherichia coli DH5a, which is capable of expressing the fungal protein. The latter was purified by the Prep-Cell System (Bio-Rad); the recovery rate of the pure protein was approximately 6%. A battery of 160 human serum samples, consisting of 64 specimens taken at the time of diagnosis from patients with PCM representing the various clinical forms plus 15 serum specimens each from patients with histoplasmosis and aspergillosis, 10 each from patients with cryptococcosis and tuberculosis, 6 from patients with coccidioidomycosis, and 40 from healthy subjects, were all tested by an indirect enzyme-linked immunosorbent assay with the purified 27-kDa recombinant protein. The latter was used at a concentration of 1.0 mg/well; there were three serum dilutions (1:1,000, 1:2,000, and 1:4,000). The experiment was repeated at least twice. The average sensitivity for both experiments was 73.4%; in comparison with the healthy subjects, the specificity for PCM patients was 87.5% while for patients with other mycoses, it was 58.7%. Important cross-reactions with sera from patients with aspergillosis and histoplasmosis were detected. The positive predictive value of the test was 90.4%. These results indicate that it is possible to employ recombinant antigenic proteins for the immunologic diagnosis of PCM and, by so doing, achieve high coverage rates. Furthermore, antigen reproducibility can now be ensured, thus facilitating inter- and intralaboratory standardization.